IMPLEMENTATION OF INFORMATION SYSTEM IN TRAVELOKA COMPANY - Amaraesty, Tasha (Dinasti International Journal of Digital Business Management, 2019)
The development of information technology has changed the world to become easier and bring development and progress in all fields. With the support of computer technology it is proven that the mechanism of long and repetitive work becomes effective and efficient. Information systems play an important role in supporting the smooth work activities in an information, how to organize data with a database system that has been supporting the performance of many agencies. Writing Purpose This would like to know how much influence an information system is implemented in a company and what are the strengths and weaknesses arising from the application of an information system in a traveloka company. This writing uses a qualitative method with literauture studies in the field of Scientific Information Systems and Information Technology (IT). Information is obtained from the artiker, module and the internet. Besides that, based on empirical experience and direct observation on the object of research.